THE FALLACY ANALYSIS OF THE PROGRAM “WAKTU INDONESIA BERCANDA” - Mulyani, Martina (English Education Department of STKIP Pasundan, 2019)
Recently, one of popular programs on TV is Waktu Indonesia Bercanda (WIB). It is a Quiz Show program that offers problems to solve and the host makes use fallacies as the core of its game. WIB offers the sense of achievement among its participants, but competitive atmosphere is hardly to find among them. This research tries to analyze the fallacies being used in WIB and figure out how such fallacies can encourage people to think critically. The research employs descriptive research design as it simply attempts to determine, describe or identify phenomena. 6 WIB from September through December were randomly selected as the subject of the research. The result shows that WIB demonstrates the use of fallacies of relevance but it avoids using argumentum ad hominem that contains personal attack. WIB may encourage the audiences and participants to think critically as fallacious arguments offered make the audiences work hard to think any possible implicatures. Eventually, WIB is the program that invites the participants and the viewers to think, evaluate and decide the answer or solution to the problem provided. In conclusion, WIB is a worth watching ShowQuiz as it is entertaining and encouraging its audience to think critically.